Quantum Key Distribution in Networking: Use of Photonic Circuits and Digital Signal Processing - Khulbe, Manisha (Research Highlights in Science and Technology Vol. 1, 2023)
In the present day today communication and increasing complexity of hacking we need to have a good control over our communication technologies.One of the primary concern is our cyber security and data transmission technology which is used for secret government information, defense data and other scientific reports.Quantum communication is one of the new emerging technology which is being adopted for confidential data transmission in all these areas.Quantum communication is based on Quantum Key Distribution(QKD). In this research we have discussed the basics of quantum key distribution with its mathematical analysis in DSP, simulation, control, applications and challenges.